2004
DOI: 10.5194/angeo-22-3099-2004
|View full text |Cite
|
Sign up to set email alerts
|

Global observations of the zonal drift speed of equatorial ionospheric plasma bubbles

Abstract: Abstract. Space-based measurements from an imager aboard the high-apogee NASA-IMAGE satellite allows for global-scale observations of nightside ionospheric densities and structure. Such a view cannot be provided by imagers in near-Earth orbit or based on the ground. The IMAGE Spectroscopic Imager (SI) isolates the Far-ultraviolet (FUV) O I 135.6 nm emission which is produced through radiative recombination of O + . These observations clearly show the distribution of FUV emissions of the equatorial airglow band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 41 publications
7
44
0
Order By: Relevance
“…The results presented above reveal a significant day-to-day variability in magnitudes of the plasma drift zonal velocities, however, the trends of the variations with the local time is similar. The plots as explained above (Figure 2-4), show that daytime plasma drifts are westward, while the night-time drifts are eastward, which is consistent with the previous results [3,4,12,15]. Similarly, increase in the plasma drifts has been seen shortly after sunset (see in Figures 2-4) as the drift reverses from westward to eastward from the day to night transition.…”
Section: Resultssupporting
confidence: 79%
“…The results presented above reveal a significant day-to-day variability in magnitudes of the plasma drift zonal velocities, however, the trends of the variations with the local time is similar. The plots as explained above (Figure 2-4), show that daytime plasma drifts are westward, while the night-time drifts are eastward, which is consistent with the previous results [3,4,12,15]. Similarly, increase in the plasma drifts has been seen shortly after sunset (see in Figures 2-4) as the drift reverses from westward to eastward from the day to night transition.…”
Section: Resultssupporting
confidence: 79%
“…They existed within the wide band-like airglow regions that correspond with the equatorial anomalies in both hemispheres. New bright airglow patches were successively created with time near the solar terminator, resulting in an apparent motion of the airglow patches to the west: actually the alternately bright and faint airglow regions moved to the east together, as has been demonstrated by Sagawa et al (2003) and Immel et al (2003Immel et al ( , 2004. The FOVs (1000 km in diameter) of the Shigaraki and Darwin all-sky imagers are indicated in Fig.…”
Section: Image Observationsmentioning
confidence: 99%
“…This camera was designed to take auroral pictures, but as demonstrated by Sagawa et al (2003) and Immel et al (2003Immel et al ( , 2004, the instrument is also sensitive enough to image the low-latitude ionosphere at night. The camera on the satellite located at 7 Re altitude can take an image with a spatial resolution of 90 km × 90 km at ionospheric altitudes and a temporal resolution of 2 min (satellite spin period).…”
Section: Observations and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Space-based far ultraviolet (FUV) optical measurements from an imager aboard the IMAGE satellite revealed that the zonal drift velocity of equatorial plasma bubbles largely depends on the longitude (Immel et al, 2004). The highest velocity was 9.9 • /h (306 m/s) around the Indian sector, while the mean speed was 6.5 • /h (200 m/s).…”
Section: Drift Velocity and Spatial Structurementioning
confidence: 99%